Methicillin-resistant Staphylococcus pseudintermedius: an underestimated risk at pet clinic - Holmstrom, Theresse (2021)
The prevalence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) as a cause of infectious disease in companion animals remains unknown. The emergence of MRSP is a challenge in veterinary medicine as multidrug-resistant strains began to emerge, resulting in treatment failures. This study provides an overview of the characterization of S. pseudintermedius strains from clinical pet samples and the prevalence of MRSP strains. A total of 123 S. pseudintermedius strains were characterized by phenotypic testing and the MALDI-TOF technique and evaluated for susceptibility to methicillin and the presence of the mecA gene. Of these, 49 (39.8%) were identified as MRSP. The results confirm the importance of monitoring resistant pathogens and the need for further studies to determine the prevalence of MRSP in companion animals. The prevalence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) as a cause of infectious disease in companion animals remains unknown. The emergence of MRSP is a challenge in veterinary medicine as multidrug-resistant strains began to emerge, resulting in treatment failures. This study provides an overview of the characterization of S. pseudintermedius strains from clinical pet samples and the prevalence of MRSP strains. A total of 123 S. pseudintermedius strains were characterized by phenotypic testing and the MALDI-TOF technique and evaluated for susceptibility to methicillin and the presence of the mecA gene. Of these, 49 (39.8%) were identified as MRSP. The results confirm the importance of monitoring resistant pathogens and the need for further studies to determine the prevalence of MRSP in companion animals.